Konflik Peran Ganda Perempuan Bekerja: Studi Pendahuluan Manajer Perempuan Bank BUMN di Provinsi Jawa Barat - Silvy Sondari Gadzali (Jurnal Administrasi Bisnis, 2021)
This study aims to explore cause factors of work-family conflict and family-work conflict among married female managers at state owned bank in West Java. The sample consisted of 93 married female managers aged between 30 and 50 years, lived together with family and directly involved in work and. The questionnaire employed with a six-point Likert scale ranging from value 1 strongly agree to value 6 strongly disagree. The data used has been ascertained normality, validity and reliability, continued by testing the differences in significance of the two groups of data through ANOVA. Findings proposed in this study, there are differences in work-family conflict that is higher in female managers, namely the level of education, the number and age of children, the level of managers that have implications for work quantity, and motivation to work. Important implications of this research are the need of attention to the emergence to consider a comfortable work environment for women, the level of job satisfaction, communication and family support and flexibility of working hours.Penelitian ini bertujuan untuk mengeksplorasi faktor-faktor yang menyebabkan konflik pekerjaan-keluarga dan konflik keluarga-pekerjaan di antara manajer perempuan menikah di Bank BUMN di Jawa Barat. Sampel terdiri dari 93 orang manajer perempuan yang telah menikah, tinggal bersama dan terlibat langsusng dengan pekerjaan serta berusia antara 30 hingga 50 tahun. Survei dilakukan menggunakan kuisioner dengan skala likert enam poin mulai dari nilai 1 sangat setuju hingga nilai 6 sangat tidak setuju. Data yang digunakan telah dipastikan normalitas, validitas dan reliabilitasnya, dilanjutkan dengan menguji perbedaan signifikansi dua kelompok data melalui ANOVA. Beberapa temuan pada penelitian ini adalah terdapat perbedaan konflik pekerjaan-keluarga yang lebih tinggi pada manajer perempuan yaitu tingkat pendidikan, jumalh dan usia anak, tingkat manajer yang berimplikasi pada kuantitas pekerjaan, dan motivasi bekerja. Implikasi penting penelitian ini adalah perhatian akan timbulnya kebutuhan untuk mempertimbangkan lingkungan kerja yang nyaman bagi perempuan, tingkat kepuasan kerja, komunikasi dan dukungan keluarga serta fleksibilitas jam kerja.